A warm-up program to reduce injuries in youth field hockey players: A quasi-experiment - Barboza, S. D.; Nauta, J.; Emery, C.; van Mechelen, W.; Gouttebarge, V.; Verhagen, E. (Journal of Athletic Training, 2019)
Context Field hockey is popular worldwide; however, it entails a risk of injury. Injuries hamper players' participation in the sport and impose a burden on public health.